Simulation of Transport Phenomena for Microwave Freeze‐Drying of Potato Slices Using Finite Element Analysis - Narathip Sujinda; Jaturapatr Varith (Food Frontiers)
ABSTRACT This research intended to investigate the transport phenomena that occur during microwave freeze‐drying (MFD) of potato slices using drying kinetics and finite element analysis (FEA). The impacts of microwave power levels and potato slice thickness on drying rate constant (DR) and average moisture diffusion (DAVG) were analyzed using MFD kinetics and were then incorporated in the simulation. It was found that the DR and DAVG were in the range of 301.3 × 10−3–775.4 × 10−3 min−1 and 1.045 × 10−10–3.336 × 10−10 m2/s, respectively. In the sublimation phase, the DR and DAVG were higher than those in the desorption phase. The DR and DAVG increased as the microwave power level increased but decreased as the thickness increased. The FEA of temperature and moisture distribution within the potato slices demonstrated the outward transfer of heat and mass from the center to the exterior and closely matched the experimental data with an error margin of within 5%, leading to the proposed schematic shrinkage model corresponding to the MFD simulation.